(untitled) (Theatrum historiae, 2016)
As a ruling class for centuries, the nobility created a complex system of symbols and rituals which jointly formed the (political) culture in Russia. Especially during the second half of the 19th century, the position of the nobility was gradually but substantially being changed. Russian society evolved towards a civic society, mainly as a consequence of the Great Reforms of the 1860s. The nobility, traditionally the most prominent social estate (soslovie), was confronted with the emancipation of the serfs, the emergence of the middle-class and its rising influence. Therefore the dominant public role of the nobility was challenged. The article is focused on the public role of the Russian nobility in the final years of the tsarist regime. The author analyzes several ways of the nobility self-presentation towards the public and tries to answer the question how far the “portrait of the nobility” was real or imagined. The analysis is based on various primary sources, foremost on the magazine Stolitsa i usaďba (City and Country Estate). The magazine, designed as a magazine of “beau monde”, was published between 1913 and 1917. It tried to present the crucial role of the nobility in Russia’s past and show its importance in the political, social and cultural life. Nonetheless such a presentation was full of contradictions. The publishers declared that the magazine was “non-political” and “non-class specific” but with the emphasis on the nobility and its distinctive role in the past and present it could hardly compete with the values of the lower classes. Even if the nobility had been able to cooperate with the industrialists and educated classes and create a new civic elite, for the peasants, it would have remained the old enemy. The lower classes refused to accept the elite as a whole, and the cultural scenario presented by Stolitsa i usaďba had no future in revolutionary Russia.